O MENINO E O BRUXO: um diálogo entre MoacyrScliar e Machado de Assis para a inserção daLiteratura Machadiana no Ensino Fundamental - Katiuscia dos Santos Soares (2023)
From the need to reflect on reading and teaching literature in elementary school, guided by readings and studies through the Professional Master's Program in Letters at the Três Lagoas Campus of UFMS, I developed an intervention proposal aimed at expanding the horizons of expectation of 8th grade students at the Fernando Corrêa State School, offering them the opportunity to know and read one of the greatest Brazilian literature writers. To achieve this, as a way of determining and meeting the students' expectations, I proposed the reading of Moacyr Scliar's "O menino e o bruxo” (The Boy and the Wizard,) a language the students are familiar with, but which also converses with Machado's work and establishes intertextual relationships that are conducive to discussions and debates in the classroom. After this reading and debate in the school environment, we read the short stories "Missa do Galo" (Midnight Mass), “A Cartomante” (The Fortune Teller) and excerpts from the novel "Dom Casmurro" in order to broaden the students' horizons of expectation. The theoretical foundation of the work was supported by the Reception Aesthetics and the study of other researchers in the Teaching of Literature. To develop the project, I intended to rely on the “Método Recepcional” (Reception Method) proposed by Aguiar and Bordini (1993). The theoretical foundation of the work is supported by the study of authors such as Antoine Compagnon (1999), Regina Zilberman (2015), Terry Eagleton (2006), and others. Keywords: Literary reading, Brazilian literature, elementary education, reception aesthetics.